Pengaruh Faktor Pengembangan Sumber Daya Manusia terhadap Tingkat Produktivitas Kerja Pegawai Negeri Sipil pada Badan Perencanaan Pembangunan Daerah Kabupaten Fakfak - Agustina Waromi; Jumadi Jumadi; Veronia Dora Wesso; Pitronela Sahetapy (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2024)
Human resource development both those working in the public sector (Civil Servants, SOE Employees, BUMD Employees) and sectors. Talking about organizational problems is inseparable from the element of human resources. The definition of human resources is people in an organization who participate and contribute according to their respective fields of duty. Human resource development will indeed not see results quickly, but in the long term, this investment will yield results that meet the expectations of the organization.In this sense, the term development will include the meaning of training and education, namely as a means of improving skills and general knowledge for human resources, in this case Civil Servants who work at the Fakfak Development Planning Agency. In the work unit at the Fakfak Development Planning Agency, it can be achieved well if there is a Civil Servant development program.This study aims to find out the influence of human resource training and development factors on the productivity of civil servants on the Fakfak Regency BAPPEDA and to find out the most dominant variables of human resource training and development factors affecting the productivity of civil servants in the Fakfak Regency BAPPEDA.The research methods used are quantitative and qualitative research methods. Based on the results of important findings of the Civil Servant Development Method research, there are 2 (two) methods of employee development, namely the on the job training method and the off the job training method.